Persistent cannabis dependence and alcohol dependence represent risks for midlife economic and social problems: A longitudinal cohort study - Cerdá, Magdalena (Clin Psychol Sci, 2016)
With the increasing legalization of cannabis, understanding the consequences of cannabis use is particularly timely. We examined the association between cannabis use and dependence, prospectively assessed between ages 18–38, and economic and social problems at age 38. We studied participants in the Dunedin Longitudinal Study, a cohort (n=1,037) followed from birth to age 38. Study members with regular cannabis use and persistent dependence experienced downward socioeconomic mobility, more financial difficulties, workplace problems, and relationship conflict in early midlife. Cannabis dependence was not linked to traffic-related convictions. Associations were not explained by socioeconomic adversity, childhood psychopathology, achievement orientation, or family structure; cannabis-related criminal convictions; early onset of cannabis dependence; or comorbid substance dependence. Cannabis dependence was associated with more financial difficulties than alcohol dependence; no difference was found in risks for other economic or social problems. Cannabis dependence is not associated with fewer harmful economic and social problems than alcohol dependence.